Angelos Kapellos. «The Orators and their Treatment of the Recent Past» - Taddei, Andrea (Lexis (Venezia, Online), 2023)
Recensione di Kapellos, A. (ed.) (2023). The Orators and their Treatment of the Recent Past . Berlin; Boston: De Gruyter, 541 pp. Trends in Classics 133.